(untitled) (Journal of Dentistry and Allied Science, 2025)
Background: Diabetes mellitus significantly increases the risk of oral health complications, yet dental care-seeking behavior among diabetic patients remains suboptimal. This study aims to assess the patterns, barriers, and influencing factors of dental care utilization and oral hygiene practices among diabetic patients. Methods: This cross-sectional descriptive study was conducted at the dental outpatient department of Community Based Medical College, Mymensingh, over a two-year period (January 2021 - December 2022). A total of 170 diabetic patients were selected using a non-probability convenient sampling technique. Data were collected through structured interviews and medical record reviews, focusing on demographic characteristics, dental care-seeking patterns, oral hygiene practices, and behavioral risk factors. Results: Only 21.18% of respondents sought dental care within six months, while 48.24% visited a dentist only in emergencies. Despite 85.29% regularly monitoring their blood sugar, 26.47% did not maintain consistent oral hygiene, and 24.71% used their fingers instead of proper instruments for cleaning. Smoking (44.71%) and betel nut chewing (41.76%) were highly prevalent, further increasing the risk of periodontal disease and oral complications. The utilization of dental prostheses was low (20%), despite evident tooth loss among participants. Conclusion: The study underscores significant gaps in preventive dental care and oral hygiene behaviors among diabetic patients. The high prevalence of risk factors, such as smoking and betel nut chewing, coupled with poor oral health-seeking behavior, calls for urgent integration of oral health education into diabetes care programs. Policy- driven initiatives focusing on awareness, accessibility, and preventive dental interventions are crucial for improving oral health outcomes in diabetic populations. Journal of Dentistry and Allied Science, Vol. 8 No 1: 14-21